2021
DOI: 10.1007/s13131-021-1923-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes of melatonin and its receptors in synchronizing turbot (Scophthalmus maximus) seasonal reproduction and maturation rhythm

Abstract: In most fish, reproduction is seasonal or periodic under the suitable conditions. In turbot (Scophthalmus maximus) farms, one of the most economically important marine flatfish species, changes in daylength could cause changes in the spawning time. In this study, to characterize the regulation of reproductive physiology following light signals, three melatonin receptors (Mtnr) investigated in turbot were named smMtnr1, smMtnr2, and smMtnr1c. Distinct expression profiles demonstrated that Mtnr mRNAs were concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In the present study, mtnr1 demonstrated higher mRNA levels than mtnr2 and mtnr3 in follicles and denuded oocytes in turbot. Zhao et al [77] found high mRNA levels of mtnr1 and mtnr2 during turbot ovarian development. The mtnr1 mRNA is significantly upregulated in oocytes and follicles after melatonin treatment, whereas those of mtnr2 and mtnr3 remained unchanged in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, mtnr1 demonstrated higher mRNA levels than mtnr2 and mtnr3 in follicles and denuded oocytes in turbot. Zhao et al [77] found high mRNA levels of mtnr1 and mtnr2 during turbot ovarian development. The mtnr1 mRNA is significantly upregulated in oocytes and follicles after melatonin treatment, whereas those of mtnr2 and mtnr3 remained unchanged in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…The developmental stages of gonads were confirmed based on ovarian and testicular histology. All of the collected turbots were classified into II, III, IV, V, and VI stages according to the dominant gamete type and characteristics ( 56 , 57 ).…”
Section: Methodsmentioning
confidence: 99%